The Effect of Online Video Marketing Promotion and Brand Awareness on Consumer Purchasing Decisions at MSMEs Make Di Fried Chicken - Madani Umpu Nikan; Diny Anggriani Adnas (Sean Institute, 2022)
Technology is an instrument that is one of the determinants of a business's success. All information is readily accessible anywhere and at any time. The advancement of technology also altered business marketing, as the previous methods can no longer captivate consumers' attention. With the advancement of technology, business owners may make it simpler to offer their products to consumers. To increase purchasing decisions, consumers must establish brand awareness, retain their perception of product quality, brand association, and brand loyalty so they remember the brand and not move to competing items. The strategy utilized in this study is a combination of quantitative and qualitative techniques. This investigation was conducted at SMEs Make Di Fried Chicken, which has Make Di Fried Chicken consumers or purchasers. The sample method employed is random sampling. In this study, data were gathered by the distribution of questionnaires. This study's respondents were individuals who purchased Fried Chicken from Make Di. According to the results obtained after processing the data with the SPSS program, online video advertising or brand recognition has a significant effect on purchasing decisions, and if these two variables are applied to the company simultaneously, online video advertising and brand recognition can simultaneously increase sales.